Relationship between suicide rate and economic growth and stock market in the People’s Republic of China: 2004–2013 - Yin HL; Xu L; Shao YC; Li LP; Wan CS (Neuropsychiatric Disease and Treatment)
Honglei Yin,1,2 Lin Xu,3 Yechang Shao,2,4 Liping Li,5 Chengsong Wan2 1Department of Psychiatry, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 2School of Public Health, Southern Medical University, Guangzhou, People’s Republic of China; 3Department of Finance, School of Economics and Commerce, South China University of Technology, Guangzhou, People’s Republic of China; 4Guangdong Academy of Medical Sciences, Guangdong General Hospital, Guangzhou, People’s Republic of China; 5Injury Prevention Research Center, Shantou University Medical College, Shantou, People’s Republic of China Objectives: The objective of this study was to estimate the features of suicide rate and its association with economic development and stock market during the past decade in the People’s Republic of China.Methods: Official data were gathered and analyzed in the People’s Republic of China during the period 2004–2013. Nationwide suicide rate was stratified by four year age-groups, sex, urban/rural areas, and regions (East, Central, and West). Annual economic indexes including gross domestic product (GDP) per capita and rural and urban income per capita were all adjusted for inflation. Variation coefficient of market index (VCMI) was also included as an economic index to measure the fluctuation of the stock market. Negative binomial regression was performed to examine the time trend of region-level suicide rates and effects of sex, age, urban/rural area, region, and economic index on the suicide rates.Results: Suicide rates of each age-group, sex, urban/rural area, and region were generally decreased from 2004 to 2013, while annual GDP per capita and rural and urban income per capita were generally increased by year. VCMI fluctuated largely, which peaked around 2009 and decreased after that time. Negative binomial regression showed that the decreased suicide rate in East and Central rural areas was the main cause of the decrease in suicide rate in the People’s Republic of China. Suicide rate in the People’s Republic of China for the study period increased with age and was higher in rural than in urban area, higher in males than in females, and the highest in the Central region. When GDP per capita increased by 2,787 RMB, the suicide rate decreased by 0.498 times. VCMI showed no significant relationship with suicide rate in the negative binomial regression.Conclusion: Suicide rate decreased in 2004–2013; varied among different age-groups, sex, urban/rural areas, and regions; and was negatively associated with the economic growth in the People’s Republic of China. Stock market showed no relationship with suicide rate, but this finding needs to be verified in a future study. Keywords: suicide rate, economic indexes, stock market, People’s Republic of China